2017
DOI: 10.18203/2349-2902.isj20172405
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic and open repair of perforated peptic ulcer

Abstract: Background: The study included patients diagnosed as perforated peptic ulcer. Outcomes are assessed by mortality and morbidity rate, operation time and hospital length of stay.Methods: On the period from January 2013 to December 2014 a total of 71 patients were operated in both facilities: 37 patients in Dubai hospital and 34 in Mafraq Hospital. Open repair with omental patch done in 34 patients (47.9%) and laparoscopically in 37 patients (52.1%). No cases of laparoscopy converted to laparotomy.Results: The da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Leakage in our study has occurred in a single case of those who were managed by laparoscopic approach. In a study done by Leong H L et al 29 , the rate of leakage seen more with laparoscopic approach, but many other studies has showed higher incidence of leakage with open repair 23,30 . This difference in rate of leakage between the two approaches and among the different studies can be attributed to many factors that affect the outcome of repair like the size of perforation and the suturing skill" especially for laparoscopic approach" which need highly skilled surgeon.…”
Section: Discussionmentioning
confidence: 97%
“…Leakage in our study has occurred in a single case of those who were managed by laparoscopic approach. In a study done by Leong H L et al 29 , the rate of leakage seen more with laparoscopic approach, but many other studies has showed higher incidence of leakage with open repair 23,30 . This difference in rate of leakage between the two approaches and among the different studies can be attributed to many factors that affect the outcome of repair like the size of perforation and the suturing skill" especially for laparoscopic approach" which need highly skilled surgeon.…”
Section: Discussionmentioning
confidence: 97%